THE EFFECTS OF INTRAPRENEURSHIP ON SOCIAL INNOVATION: A RESEARCH IN İZMİR - Esen, Murat; Şekerdil, Reşat (International Journal of Contemporary Economics and Administrative Sciences, 2017)
Social innovation is a realized action that transfers from profits to social needs by using entrepreneurial skills. Social innovation is an action which is carried out by transferring profits to social needs with the help of entrepreneurial skills Non-profit organizations and businesses organizations have developed social implementations at local, regional and national level to overcome social problems. To overcome social problems, organizations can encourage their employees’ entrepreneurial performance. Intrapreneurship must be supported in an organization to need employees who are more innovative, self-confident, proactive and able to take risk. Employees are required to be more innovative, self-confident, proactive and likely to take risks in order to support intrapreneurship in an organization. Organizations will both develop their own special abilities and be able to change the way of competing with new products, technologies, social relations in the market. The purpose of this study is to examine the effect of Intrapreneurship on social innovation. In order to test construct validity of the study; factor analysis, correlation analysis were used to measure the severity and direction of the relationship between the variables and regression analysis was used to measure causality between variables. As a result of the research; while “Innovation and Proactivity” which is a sub-dimension of entrepreneurship, is effective on social innovation, the performance of "risk taking and self-confidence", another sub-dimension of entrepreneurship, is not effective on social innovation. Suggestions have been made to the organizations, managers, stakeholders, employees in the light of findings.